2017
DOI: 10.2147/ott.s130087
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of circulating tumor cells in organ metastases, prognosis, and T lymphocyte mediated immune response

Abstract: Circulating tumor cells (CTCs) possess profound influence on tumor metastases and disease progression. This study aimed to investigate the correlation of CTCs with clinical characteristics and T-cell immunity, and to explore whether CTCs and the subpopulations can serve as an independent prognostic factor in advanced non-small cell lung cancer (NSCLC). A prospective study was conducted in late stages of NSCLC patients. The levels of overall CTCs and the three subpopulation CTCs were enumerated using the CanPat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…In metastasis, CTLs exert an anti-metastatic effect in bone metastasis (Bidwell et al 2012), while prospective analyses of lung and breast cancer patients established an opposite correlation between the level of circulating cancer cells and T cells in peripheral blood (Mego et al 2016;Sun et al 2017). These data extend to clinical trials reporting the therapeutic efficacy of immune checkpoint inhibition in metastatic carcinomas (Di Giacomo et al 2012;Queirolo et al 2014;Motzer et al 2015;Furudate et al 2016;Goldberg et al 2016;Pai-Scherf et al 2017).…”
Section: T Cellsmentioning
confidence: 85%
“…In metastasis, CTLs exert an anti-metastatic effect in bone metastasis (Bidwell et al 2012), while prospective analyses of lung and breast cancer patients established an opposite correlation between the level of circulating cancer cells and T cells in peripheral blood (Mego et al 2016;Sun et al 2017). These data extend to clinical trials reporting the therapeutic efficacy of immune checkpoint inhibition in metastatic carcinomas (Di Giacomo et al 2012;Queirolo et al 2014;Motzer et al 2015;Furudate et al 2016;Goldberg et al 2016;Pai-Scherf et al 2017).…”
Section: T Cellsmentioning
confidence: 85%
“…A reduction in lymphocyte numbers would undoubtedly reduce the host anti‐tumor immune response and promote the metastatic potential of the tumor. Several studies have also shown that low lymphocyte counts are significantly associated with poor survival in lung cancer patients 19, 20. Therefore, peripheral blood lymphocyte counts have been used as an important constituent marker not only in PLR but also in numerous prognostic indicators, such as NLR and the prognostic nutritional index 6, 7, 8…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that low lymphocyte counts are significantly associated with poor survival in lung cancer patients. 19,20 Therefore, peripheral blood lymphocyte counts have been used as an important constituent marker not only in PLR but also in numerous prognostic indicators, such as NLR and the prognostic nutritional index. [6][7][8] The elevation of platelets could promote the metastatic potential of tumor cells through several pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The antimetastatic effect of T-cell activation has been documentedanalysis in bone metastasis from breast carcinoma shows that cytotoxic CD8+ T cells, in an interferon-dependent manner, play a primary role in antimetastatic defense [65]. A clinical prospective study with 31 lung cancer patients revealed that the levels of circulating cancer cells are positively correlated with bone metastasis, but negatively correlated with circulating T-cell levels [66]. Similar conclusions arose from a study of 65 breast cancer patients, whose levels of circulating tumor cells correlate with a defective adaptive immune response [67].…”
Section: Metastasis-associated T Cellsmentioning
confidence: 99%